Validity and reliability of the Turkish version of the selfperceived food literacy scale: Self-Perceived Food Literacy Scale - Tarı Selçuk, Kevser; Çevik, Celalettin; Baydur, Hakan; Meseri, Reci (Progress in Nutrition, 2020)
Purpose: The present study was aimed at adapting the Self-Perceived Food Literacy Scale intoTurkish and investigating its psychometric properties. Methods: This study was conducted with 391 adultsaged ≥18 years living in a provincial center. This five-point likert scale consists of 29 items and 8 sub-scales.In the analysis of the study data, cronbach’s alpha values, ıntraclass correlation coefficient and item-total andinter-scale correlation coefficients were calculated, and the confirmatory factor analysis and linear regressionanalysis were performed. Results: The cronbach’s alpha value was 0.84, 0.70, 0.76, 0.61, 0.89, 0.69, 0.90, 0.92for the subscales respectively (food preparation skills, resilience and resistance, healthy snack styles, socialand conscious eating, examining food labels, daily food planning, healthy budgeting, healthy food stockpiling)and 0.83 for the overall scale. The test-retest intraclass correlation coefficient is between 0.80 and 0.96.The goodness of fit values of the confirmatory factor analysis are between 0.062-0.93. Conclusion: The Self-Perceived Food Literacy Scale adapted to Turkish society is a valid and reliable scale.